PENGARUH PENGGUNAAN FLASH CARD TERHADAP KEMAMPUAN MENGENAL LAMBANG BILANGAN PADA ANAK USIA 4-5 TAHUN DI TK IRSYADUL UMMAH KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI - Resti, Mizalia; Novianti, Ria; ', Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on field observations of the ability to recognize the numeral symbol children not develop optimally. So it is necessary to use flash card application This study aims to determine the effect of using flash cards the ability to recognize the number symbol 4-5 years old children at Irsyadul Ummah kindergarten District Kuantan Mudik District of Kuantan Singingi. The sample used in this study 15 people protÃ©gÃ©. The data collection techniques were used that observation and documentation. Were analyzed using t-test using SPSS 16.0. The study hypothesis is the use of flash cards activity has an effect on the ability to recognize the numeral symbol 4-5 years old children at Irsyadul Ummah kindergarten District Kuantan Mudik District of Kuantan Singingi. It can be seen from the analysis of data obtained t = 10.879 and Sig. (2-tailed) = 0,000. Because Sig. (2-tailed) <0.05, it can be concluded that there are differences in the ability to recognize the numeral symbol the epitome of a significant of children after the use of flash cards for learning. So it means Ho rejected and Ha accepted which means there is a very significant difference between before and after the experiment to apply the use of flash cards. The effect of using flash cards to the ability to recognize the number symbol 4-5 year old children at Irsyadul Ummah kindergarten District Kuantan Mudik District of Kuantan Singingi amounted to 33,5%.